LncRNA NEAT1 Promotes Gastric Cancer Progression Through miR-17-5p/TGFβR2 Axis Up-Regulated Angiogenesis - Xu, Yangwei; Li, Yanyan; Qiu, Yue; Sun, Fei; Zhu, Guifang; Sun, Jingbo; Cai, Guixing; Lin, Wanmei; Fu, Yun; Wu, Hongmei; Jiang, Shanshan; Wen, Zhihui; et al. (Frontiers in Cell and Developmental Biology, 2021)
Background: Long noncoding RNAs (lncRNAs) have been indicated to play critical roles in gastric cancer (GC) tumorigenesis and progression. However, their roles in GC remain to be further elucidated. Methods: RT-qPCR and fluorescence in situ hybridzation (FISH) were conducted to detect the expression of lncRNA NEAT1 in GC tissues and cell lines. Gene Set Enrichment Analysis (GSEA) was performed to screen out potential phenotypes and pathways NEAT1 may participate in. NEAT1-silenced AGS and MGC803 cells were constructed and a series of functional experiments to investigate the roles of NEAT1 in GC angiogenesis both in vitro and in vivo. RNA pull down and luciferase reporter assays were utilized to illustrate the mechanisms underlying the functions of NEAT1 in GC. Results: We observed that NEAT1 was upregulated in most GC specimens and cell lines. NEAT1 high was correlated with poor prognosis of GC patients. In vitro experiments showed that NEAT1 promoted GC angiogenesis by enhancing proliferation, migration and tube formation ability of endothelial cells. Mechanism researches revealed that NEAT1 could competitively sponge miR-17-5p which targeted TGFβR2 directly. Subsequently, activate TGFβ/smad pathway by following with upregulation of a series of classical proangiogenic factors especially VEGF. Conclusion: The study unveiled that the lncNEAT1/miR-17-5p/TGFβR2 axis is a novel mechanism in GC angiogenesis. Disrupting this axis may be a potential strategy for GC treatment.